The experiences of expatriate mothers regarding pregnancy, childbirth and motherhood in the host city Cape Town, South Africa - Penduka, Annaloice (University of Cape Town, 2020)
The study explored the experiences of expatriate mothers' pregnancy, childbirth and motherhood in a host city. This included identifying how expatriate mothers access public healthcare, and adapt to motherhood in a host country in a subsequent pregnancy. These expatriate mothers had previously experienced childbirth in their country of origin. A descriptive qualitative approach was utilised as it describes individuals' lived experiences. Purposive sampling was chosen and I had an in-depth conversation with nine expatriate mothers. Thematic analysis was used to identify themes and sub-themes. Findings: The participants established that antenatal care was easily accessible. Mothers were confronted with a lack of respectful care in labour wards. They also had personal challenges. This all led to the development of the four themes. These are: expatriate mothers' need for support; organised antenatal healthcare; high cost of living; as well as labour and childbirth challenges in Cape Town (public healthcare). These revealed mothers need support to manage motherhood in a different setting. Further, the expatriate mothers rely on their husbands as their main support in the host city. Recommendations: An emphasis on teaching of respectful maternity care in midwifery is needed, the availability of more and highly skilled and caring midwives and the need for support groups for expatriate mothers.